Incomplete articular-side repair increase re-tear rate in full-thickness rotator cuff tears - Kyung Cheon Kim; Woo-Yong Lee; Hyun Dae Shin; Sun-Cheol Han (Journal of Orthopaedic Surgery, 2018)
Purpose: This study compared the functional outcome and repair integrity of arthroscopic rotator cuff repair according to articular-side repair state in full-thickness tears. Methods: We prospectively enrolled 80 consecutive patients with full-thickness rotator cuff tears of 1.5–3.5 cm at the anterior to posterior dimension. These patients were divided into two groups according to intraoperative articular-side repair state during operation: complete and incomplete repair groups. Repair integrity was evaluated at 6 months after the operation by magnetic resonance image or ultrasonography. Clinical outcomes were evaluated at 1 year and 2 years postoperatively. Four outcome measures were used in this study: visual analog scale pain score, American Shoulder and Elbow Surgeons (ASES) score, the Shoulder Rating Scale of the University of California at Los Angeles (UCLA) score, and range of motion. Results: At 2-year follow-up, the average UCLA, ASES, and constant score improved significantly to 32.46, 87.94, and 79.69, respectively, in the complete group and to 32.50, 87.65, and 78.92, respectively, in the incomplete group. The UCLA, ASES, and constant score improved in both groups postoperatively (all p s < 0.000); however, there was no significant difference between the two groups ( p = 0.960, 0.921, and 0.796, respectively). The re-tear rate was 13.7% in the shoulders that underwent complete repair and 33.3% in the shoulders that underwent incomplete repair; this difference was statistically significant ( p = 0.041). Conclusion: Regardless of the repair state of articular-side rotator cuff, the arthroscopic rotator cuff repair resulted in comparable functional outcomes between two groups at short-term follow-up. However, patients who repaired articular-side rotator cuff incompletely revealed higher re-tear rate after operation than those who repaired completely.